The mental health effects of pet death during childhood: is it better to have loved and lost than never to have loved at all? - Crawford, Katherine M.; Zhu, Yiwen; Davis, Kathryn A.; Ernst, Samantha; Jacobsson, Kristina; Nishimi, Kristen; Smith, Andrew D. A. C.; Dunn, Erin C. (European Child & Adolescent Psychiatry, 2021)
Pet ownership is common. Growing evidence suggests children form deep emotional attachments to their pets. Yet, little is known about children's emotional reactions to a pet's death. The goal of this study was to describe the relationship between experiences of pet death and risk of childhood psychopathology and determine if it was "better to have loved and lost than never to have loved at all". Data came from the Avon Longitudinal Study of Parents and Children, a UK-based prospective birth cohort (n = 6260). Children were characterized based on their exposure to pet ownership and pet death from birth to age 7 (never loved;loved without loss; loved with loss). Psychopathology symptoms at age 8 were compared across groups using multivariable linear regression. Psychopathology symptoms were higher among children who had loved with loss compared to those who had loved without loss (β = 0.35, p = 0.013; 95% CI = 0.07, 0.63), even after adjustment for other adversities. This group effect was more pronounced in males than in females. There was no difference in psychopathology symptoms between children who had loved with loss and those who had never loved (β = 0.20, p = 0.31, 95% CI = −0.18–0.58). The developmental timing, recency, or accumulation of pet death was unassociated with psychopathology symptoms. Pet death may be traumatic for children and associated with subsequent mental health difficulties. Where childhood pet ownership and pet bereavement is concerned, Tennyson's pronouncement may not apply to children's grief responses: it may not be "better to have loved and lost than never to have loved at all".